Adaptasi Nelayan Manogo di Tengah Nasib yang Terombang-ambing di Desa Bakambat Kabupaten Banjar - Sibawaihi, Muhammad; Hakim, Arif Rahman (Huma: Jurnal Sosiologi, 2024)
Manogo fishermen are a source of livelihood for the majority of the people of Bakambat Village, who are currently facing various complexities, such as environmental factors and others. This research aims to look at the adaptation patterns made by manogo fishermen from the problems they face, both at sea and on land. This research uses a qualitative method with a descriptive approach. The data collection techniques used were observation, interviews and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. This research uses adaptation theory from John William Bennett. The results of the research show that manogo fishermen in Bakambat Village face various problems which include environmental factors, the use of illegal fishing gear by other fishermen, coal barges passing through the fishing areas of manogo fishermen, as well as regulations related to illegal logging. The problems faced have a huge impact on the economy of manogo fishermen, as well as threatening the local knowledge and wisdom of the people in Bakambat Village about manogo. The various problems faced gave rise to adaptation patterns that were implemented, such as moving fishing locations, installing several nets, moving fishing locations, variations in processed products, seeking compensation costs from coal barges, and the emergence of resistance. The adaptation pattern implemented is nothing more than a way for the livelihood of manogo fishermen to continue to survive, as well as how local knowledge and wisdom of manogo continues to exist for generations to come. It is hoped that the adaptation patterns implemented by manogo fishermen will continue to develop, such as the use of fishing gear to the processing process and continue to maintain Manogo as an identity even though big problems lie ahead.